МАКЕДОНСКИОТ РОМАН И ТРАНЗИЦИЈА (Филологические заметки, 2019)
The Macedonian novelistic production in the last fifteen years is deeply determined by the concepts of transition, cultural transition and identity. These tendencies are establishing two images that present the relation Macedonia-Europe regarding the space and both synchronic (presentpresent) and diachronic (present-past) level regarding the time. The first type produces the collective, ethnical identity (the novels “Aristocrat” by Ermis Lafazanovski and “The eight world wonder” by Jordan Plevnes) and the second one produces the individual identity (“The hidden camera” by Lidija Dimkovska, “Dzahis and the dog exterminators” by Pajo Avirovic and “The Peeper” by Aleksandar Prokopiev). This classification is relational because identity is not one and only and established forever, but it is “complex and heterogeneous”. Therefore, the collective identity contains the individual one, so their precise separation is not feasible.